RESEARCH MAPPING ON CREDIT RISK IN ISLAMIC AND CONVENTIONAL BANKING - Budianto, Eka Wahyu Hestya (Al-Infaq: Jurnal Ekonomi Islam, 2023)
This study aims to determine the development of research around credit risk in Islamic and Conventional Financial Institutions. The research was conducted from 1975 to 2022 by searching national and international journals indexed by Google Scholar, Sinta, and Scopus via the Perish/Harzing application with the keyword "Credit Risk." Based on the search results, there were 1139 research articles, then inputted into the VOSviewer application and analyzed descriptively through a literature review study. The results showed that the number of publications had increased significantly every year. Furthermore, based on the results detected using the VOSviewer application, research related to credit risk is divided into 5 clusters. Meanwhile, based on the results of a literature review study, there are 13 main themes related to credit risk in Islamic and Conventional Banking.